Paroxysmal extreme pain disorder associated with a mutation in SCN9A gene – Case report and own experiences - Szczupak, Mateusz; Wierzchowska, Jolanta; Cimoszko-Zauliczna, Maria; Kobak, Jacek; Kosydar-Bochenek, Justyna; Radys, Wojciech; Szlagatys-Sidorkiewicz, Agnieszka; Religa, Dorota; Krupa-Nurcek, Sabina (Frontiers in Neurology, 2024)
IntroductionPain is an unpleasant sensory and emotional experience, influenced by various factors. Paroxysmal extreme pain disorder (PEPD) is a rare genetic condition characterized by sudden bouts of pain accompanied by autonomic symptoms.Material, methods and aimThis manuscript presents the case of a 9-year-old boy with paroxysmal extreme pain syndrome and provides a review of the literature. Additionally, a genealogical analysis of the boy’s family was conducted to determine the total number of affected family members. The clinical data included an analysis of genetic tests to identify the mutation confirming PEPD.Result and conclusionA mutation in the SCN9A gene causes the disease, and due to the small number of patients worldwide (around 500, according to literature reports), an effective method of preventing extreme pain attacks had not been established at the time of writing this manuscript. Based on information from scientific sources and the authors’ experiences, it can be firmly stated that various, often difficult-to-identify factors cause paroxysmal extreme pain. This syndrome necessitates further research and the exploration of effective treatment methods.